2013
DOI: 10.1258/jrsm.2012.120240
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the state of health research in the Eastern Mediterranean Region

Abstract: Member states across the Eastern Mediterranean region face unprecedented health challenges, buffeted by demographic change, a dual disease burden, rising health costs, and the effects of ongoing conflict and population movements - exacerbated in the near-term by instability arising from recent political upheaval in the Middle East. However, health actors in the region are not well positioned to respond to these challenges because of a dearth of good quality health research. This review presents an assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(117 citation statements)
references
References 17 publications
5
111
1
Order By: Relevance
“…1 In a separate paper, Haworth and others explain why the Hajj pilgrimage offers a unique opportunity to test the effectiveness of influenza prevention strategies that require a large sample size. 2 These issues may seem distant but focusing on advances in science and improvements in health can be a unifying force.…”
mentioning
confidence: 99%
“…1 In a separate paper, Haworth and others explain why the Hajj pilgrimage offers a unique opportunity to test the effectiveness of influenza prevention strategies that require a large sample size. 2 These issues may seem distant but focusing on advances in science and improvements in health can be a unifying force.…”
mentioning
confidence: 99%
“…limited budgets for health research (6). Policy-makers in these countries may be also unaware of the importance of health research in improving health systems and public health, as reported by some respondents.…”
Section: Discussionmentioning
confidence: 99%
“…The tool was a modified version of tools used in previous regional/ global mapping exercises (3,6,(10)(11)(12)(13)(14)(15) and consisted of 6 sections, each comprising several questions on: background information; institutional characteristics; scope of research; training and capacity building; ethics, leadership and governance; and resources (human, financial and technical). In addition, participants were asked to provide narrative remarks reflecting challenges (national, financial, human resources and technical) faced when conducting research within their respective institutions.…”
Section: Health Research Institutions Mapping Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…This is certainly emphasized by the World Health Organization (WHO), which urges that mobilizing and sustaining the sufficient resources and required potentials (2) are important to generate high-quality knowledge to support evidence-informed decision-making (3). HRSRIC should be considered in any attempt to analyse the HRS, and this is clearly and fundamentally featured in conceptual HRS frameworks that help in better system understanding through a wide-range analysis approach (4)(5)(6), as other similar studies found (7)(8)(9). These frameworks portrayed the HRS fabric, including HRSRIC, which forms a solid base and an imperative priority for any HR advancement.…”
Section: Introductionmentioning
confidence: 99%